Working with the elderly: Factors associated with the interest of nursing students in Brazil and Chile - Barreto Colichi, Rosana Maria [UNESP]; Jimenez Figueroa, Andres Eduardo; Urrutia, Verónica Gómez; de Carvalho Nunes, Hélio Rubens [UNESP]; Molina Lima, Silvana Andrea [UNESP] (Revista Baiana de Enfermagem, 2021)
Objective: to identify factors associated with the interest in working with the elderly as a future job market among nursing students from Brazil and Chile. Method: cross-sectional analytical study, conducted between March and September 2018, including 885 nursing students. A form was used with sociodemographic information related to family and areas of activity and the Family Support Perception Inventory. Statistical analysis included bivariate associations and multiple logistic regression models. Results: 27.5% of the students considered working with the elderly as a possible professional performance, without association with family variables. There were positive associations between those who attended public institutions and cited working with children and negative associations among older students. Conclusion: for most nursing students in Brazil and Chile, working with the elderly was not considered as a possibility of professional performance; this possibility was lower among older students and higher among students from public institutions.
Trabajar con ancianos: Factores asociados con el interés de los estudiantes de enfermería en Brasil y Chile
Trabalhar com idosos: Fatores associados ao interesse de estudantes de enfermagem no Brasil e no Chile
Keywords: Aging; Intention; Labor Market; Nursing Education; Nursing Students